Design and perspective of amorphous metal nanoparticles from laser synthesis and processing. Issue 19 (10th May 2021) - Liang, Shun-Xing; Zhang, Lai-Chang; Reichenberger, Sven; Barcikowski, Stephan
Abstract : Pulsed laser strategies ( i.e. pulsed laser ablation and fragmentation in liquid) have been reviewed with a focus on the synthesis and processing of amorphous metal nanoparticles. The possible formation criteria and mechanism have been discussed. Abstract : Amorphous metal nanoparticles (A-NPs) have aroused great interest in their structural disordering nature and combined downsizing strategies ( e.g. nanoscaling), both of which are beneficial for highly strengthened properties compared to their crystalline counterparts. Conventional synthesis strategies easily induce product contamination and/or size limitations, which largely narrow their applications. In recent years, laser ablation in liquid (LAL) and laser fragmentation in liquid (LFL) as "green" and scalable colloid synthesis methodologies have attracted extensive enthusiasm in the production of ultrapure crystalline NPs, while they also show promising potential for the production of A-NPs. Yet, the amorphization in such methods still lacks sufficient rules to follow regarding the formation mechanism and criteria. To that end, this article reviews amorphous metal oxide and carbide NPs from LAL and LFL in terms of NP types, liquid selection, target elements, laser parameters, and possible formation mechanism, all of which play a significant role in the competitive relationship between amorphization and crystallization. Furthermore, we provide the prospect of laser-generated metallic glass nanoparticles (MG-NPs) from MG targets. The current and potential applications of A-NPs are also discussed, categorized by the attractive application fields e.g. in catalysis and magnetism. The present work aims to give possible selection rules and perspective on the design of colloidal A-NPs as well as the synthesis criteria of MG-NPs from laser-based strategies.